IMPACTS OF COOPERATION? COMPARING THE NATIONAL DEVELOPMENT BANKS OF BRAZIL AND ANGOLA - Alencar Silva Mello, Patricia; Matos Marinho, Sarah Morganna (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
Importing institutional solutions is a theoretical alternative to cases non-identified with the transplants approach. Studying the context of the creation of the Brazilian development banks and the Angolan bank, the BDA, illustrates the utility of such approach. Judgment regarding convenience and suitability of institutional solutions is beyond our scope in this paper, which also did not aim at contributing to the critical literature on institutional transplants. By taking an exploratory qualitative research based on the comparison of cases, our core purpose was reflecting if Angola imported the Brazilian institutional model when it decided to create the BDA, noting as well how it has been consolidating locally.